INTERNALIZATION OF CHARACTER EDUCATION THROUGH THE APPLICATION OF WEB-BASED GENRE APPLICATIONS - Trisnawati, Trisnawati; Pandiangan, Andre Yoel (STMIK Pringsewu, 2022)
Healthy youth is the progress of a nation. Marriage under the age of 18 is a problem that must be faced by some young people in the world (especially in developing countries like Indonesia). The high risk of sex outside of marriage has attracted the attention of the government. One of the government efforts related to adolescent health is to provide sex education to adolescents so that they understand the risk of infectious diseases caused by free sex and drug abuse. In addition, the rapid development and advancement of information technology have changed all attitudes, styles, and ways of thinking of modern humans. Even today, the culture of dating, free sex, and the use of illegal drugs has become commonplace and even commonplace among young people. The aim of this study is to provide personality education through the website-based Gendre application to enable young people to understand the negative effects of premarital sex or trying to use illegal drugs. The author hopes that the younger generation can avoid a lifestyle that has a negative impact on their own future and the future of the Indonesian nation. From this research, the Genre website is produced and the testing on this system uses the User Acceptance Testing method, which is a questionnaire with 4 stages, namely user reactions to the system, and reactions. users to the system interface, user reactions in operating the system, and user reactions to system functionality. and the search results were calculated using a Likert scale, and the number of responders was 10 people. From the test on this research, it is concluded that the test results using a Likert scale are 88% of respondents like the results of this website.